Social determinants of health, health behaviors, and general health among colorectal cancer survivors: A cross-sectional study - Youran Lee; Susan G. Silva; Rosa M. Gonzalez-Guarda (PLoS ONE, 2025)
Purpose Colorectal cancer is the second leading cause of cancer death globally, yet the extent to which social determinants of health (SDOH) and health behaviors contribute to disparities in general health status among colorectal cancer survivors (CRCS) is not well understood. This study aimed to identify SDOH associated with general health among CRCS and determine whether the number of current positive health behaviors mediated these associations. Methods Cross-sectional data from 655 CRCS participating in the 2017, 2019, or 2021 Behavioral Risk Factor Surveillance System survey were analyzed. The outcome was poor/fair general health. SDOH included age, gender, race/ethnicity, education, marital status, employment, income, and three healthcare accessibility factors. Current positive health behaviors were fruit intake, current vegetable intake, regular exercise, non-smoker, and non-user of alcohol. Multivariable regression covarying for chronic conditions was used to examine the relationship between the SDOH, health behaviors, and general health. Results The sample was primarily older adults (79.5%) and Non-Hispanic White (75.2%). Most had healthcare access (95.5%), with 39.5% having multiple chronic conditions and 32.6% reporting poor/fair health. Odds of poor/fair health were significantly greater among those unmarried (aOR = 1.90, 95% CI = 1.08, 3.33, p = .0263), unemployed (aOR = 1.92, 95% CI = 1.09, 3.38, p = .0243), and reporting multiple chronic conditions (aOR = 2.97, 95% CI = 1.46, 6.01, p = .0026). The number of current positive health behaviors did not mediate these associations. Conclusion Family support and socioeconomic factors are important social contributors to general health disparities among CRCS. Establishing comprehensive social support systems is important to enhance the general health of CRCS.